Polycystic ovarian syndrome in adolescents: From diagnostic criteria to therapeutic management - Nicolaides, Nicolas C.; Matheou, Andreas; Vlachou, Florentia; Neocleous, Vassos; Skordis, Nicos (Acta Biomedica Atenei Parmensis, 2020)
Polycystic ovarian syndrome is a common endocrinologic condition diagnosed in women of childbearing age. It is primarily associated with androgen excess and ovarian dysfunction, which contribute to menstrual irregularity, oligo-anovulation, infertility, hirsutism and acne. It is associated with several systemic conditions, including type 2 diabetes mellitus, cardiovascular disease, obesity and neuropsychological disorders. The exact pathophysiology and clinical features are highly variable and, thus, there is still controversy in defining the diagnostic criteria. In this review, we outline the main diagnostic criteria, discuss the mechanisms involved in the complex pathogenesis, and present the associated clinical manifestations and therapeutic management of the syndrome in adolescents.